Design thinking new product development essentials from the PDMA - edited by Michael Luchs, Scott Swan, Abbie Griffin (Hoboken, New Jersey John Wiley & Sons Inc, 2015)
Develop a more systematic, human-centered, results-oriented thought process
Includes bibliographical references and index.
Keywords: Product design